Dinamika Homesick dan Regulasi Emosi: Peran Konseling Santri di Pesantren Al- Amanah Kudus (Jurnal Penelitian, 2025)
Pesantren serves not merely as an educational institution but as a living space demanding simultaneous social, emotional, and spiritual adaptation. This study explores the dynamics of homesickness experienced by students and the role of counseling services in reconstructing their emotional narratives at Al-Amanah Islamic Boarding School in Kudus. Employing a narrative ethnographic approach, the research captures students’ lived experiences of homesickness, their coping strategies, and how counselors facilitate the transformation of emotional meaning. Findings reveal that homesickness narratives evolve from burdensome emotions into sources of spiritual insight, shaped through the mediating interplay of pesantren traditions, religious symbols, and counseling dialogues. Counseling in the pesantren context functions not only as a therapeutic tool but also as a cultural practice that reshapes students’ understanding of distance, closeness, and independence. This study underscores the importance of narrative and culturally grounded counseling approaches in fostering students’ emotional adaptation holistically.